The impact of the learning environment on students’ creative competence: A study at Thai Nguyen University of Education - Kim, Thu Dam Thi; Anh, Nguyen Thi Lan (Journal of Advanced Education and Sciences, 2026)
This study examines the impact of the learning environment on the creative competence of pre-service teachers using a quantitative approach with a sample of 240 students. The findings indicate that the learning environment has a positive influence on students’ creativity, with teaching methods and experiential learning activities identified as the most influential factors in enhancing flexibility, problem-solving ability, and willingness to experiment with new approaches. Psychological and social elements, including teacher encouragement, openness, and peer collaboration, also play a significant role in fostering a supportive climate for creative engagement. In contrast, structural factors such as physical facilities and institutional policies show relatively weaker effects, suggesting that creativity is more strongly shaped by pedagogical practices and interactive learning processes than by material conditions. Furthermore, the results reveal that students demonstrate stronger creativity in terms of processes rather than outcomes, indicating a gap between idea generation and the production of original and valuable products. These findings highlight the importance of promoting learner-centered pedagogy, experiential learning, and supportive classroom environments to effectively develop creative competence in teacher education.